Reflexivity woven through qualitative health research: A researcher's experience - Kuhnke, Janet L.; Jack-Malik , Sandra (European Journal for Qualitative Research in Psychotherapy, 2024)
Engaging in a qualitative, autobiographical research project as a nurse researcher, provided a place and space to explore my reflexive ways of being. This article focuses on describing the reflexivity practices in which I engaged throughout a twenty-four-month research study. This article focuses on a reflexivity practice while researching recovery from eating disorders, and while living during the global coronavirus pandemic. Throughout the research project, and in efforts to deepen understandings of the reflexivity experiences, I read related literature and focused on best and promising practices for eating disorder assessment, treatment, and management. I sought to scaffold and find a place to safely approach and respond to the dataset and artifacts. As an expression of reflexivity alongside the research, I journaled and created art as a medium to illustrate my practice. Simultaneously, I engaged in related conversations with trusted peers. In this work I am therefore both a participant and researcher (Roberts, 1982). Guiding this work were my understandings of stories and lived experiences which, in time, allowed me to create and live out new stories. Linda Finlay's (2012) approach to reflexivity informed and guided the project. As well, Dewey's (1934, 1958) writings on art and nature as experience allowed me to be mindful of my reflexivity practices. Finally, Susan Finley's (2011) critical arts-based notions gave me permission to create in multiple mediums as part of the reflexivity process. Four themes emerged from the reflexive thematic analysis: 1) the importance of scheduling time to conduct reflexivity activities and inquire into and understand responses; 2) the importance of spiritual care; 3) the role of trusted, supportive peers can help re-story shame; 3) the process of living out future, educative stories are possible; and 4) a reflexive practice can include embodied responses.